"A Lot Takes Place Digitally Now, So It Can Be Good to Train on It'': A Large-Scale Repeated Cross-Sectional Study on Recording Live-Streamed Educational Activities among Health, Social, and Education Students - Kari Almendingen; Torhild Skotheim; Ellen Merethe Magnus (MDPI AG, 2022)
Audio recording is used in language and music education as an active learning resource to help students reflect on their performance and improve their accuracy. Recordings may be used to provide feedback on both verbal and nonverbal skills and to prepare professional candidates for talking to vulnerable users or other professionals. Despite its potential, recording among health, social, and education candidates to help them improve their digital relations skills is usually not part of pre-service training. Therefore, the objective was to assess the extent to which professional students were affected by recordings in live-stream settings and to explore their perspectives through qualitative elaboration. The design was a repeated cross-sectional mixed-methods study conducted in 2020-2021 (n = 1040 and n = 2238, response rate: 46% and 45%, respectively). Although participation was reduced, active online participation was low, regardless of recording practice. Educational background and age were determinants of active participation, regardless of the recording practice. Active students were the least affected by recording. Students wanted more recordings. Their perspectives revolved around different practices, privacy issues, and the recording used for traditional knowledge transfer instead of active learning. Although the General Data Protection Regulation must be met, we suggest that recording is an underused learning resource.